Professional safety in a career choice period: empirical explication of professional reserves of a personality - Virna, Zhanna P.; Lazorko, Olga V.; Koshyrets, Volodymyr V. (Psychological Counseling and Psychotherapy, 2019)
The article represents theoretical grounding and empirical determination of psychological reserves of a personality’s professional safety in its career choice period. The main aspects of the suggested research position of theoretical analysis and program development of empirical diagnostic research have been outlined. Theoretical conceptualization of the problem touches consideration of personality’s professional safety aspects in a career choice period and specifics experience of social satisfaction of young people as a feature of personality’s readiness to improve the quality of professional and personal life in future. The developed program of empirical research as well as the complex of used methods of mathematical processing of the research results allows to concretize the content of social frustrational determination of a career choice in senior school age: the increased sequence of social frustration level parameters is reflected in the change of its psychological features from the emancipated independence and rational responsibility to the intellectual estrangement.